AKTIVISME TASAWUF MENURUT FETHULLAH GÜLEN - Haderi, Anang (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2015)
Abstract: This article will elaborate the sufism thought of Fethullah Gulen. He has transformed Sufism from purely spiritual experience turned into an activity that is directly in contact with the issue of Muslims and human beings on this earth. Two of the most prominent organizer of the mystical transformation is education and the world peace movement. He tried to bring peace to the world across cultures, religions and ethnicities. The thought pattern of Gülen which is based on religious values and the universality has created a concept which is more popular in the community, but do not abandon spiritual values. The transformation of ideas and concepts of sufism who taught the importance of devotion to others, selflessness and love of neighbor. Abstrak: Artikel ini akan mengelaborasi pemikiran tasawuf Fethullah Gulen. Ia telah mentransformasikan tasawuf dari yang hanya bersifat pengalaman spiritual berubah menjadi sebuah aktivitas yang langsung bersentuhan dengan persoalan umat Islam dan manusia di bumi ini. Dua agenda yang paling menonjol dari transformasi sufistiknya itu adalah pendidikan dan gerakan perdamaian dunia. Ia berupaya mewujudkan perdamaian dunia lintas budaya, agama maupun etnis. Pola pemikiran Gülen yang dilandasi nilai-nilai keagamaan dan universalitas telah menciptakan konsep yang lebih memasyarakat namun tidak meninggalkan nilai-nilai spiritual. Transformasi dari pemikiran dan konsep tasawwuf yang mengajarkan pentingnya pengabdian kepada orang lain, tidak mementingkan diri sendiri dan cinta terhadap sesama. Keywords: transformasi, tasawuf, perdamaian, pendidikan, generasi emas.